Taxonomic study of Bornean species of Utivarachna Kishida, 1940 (Araneae: Trachelidae), with the description of a new species - Yamasaki, Takeshi; Hashimoto, Yoshiaki; Endo, Tomoji; Hyodo, Fujio; Itioka, Takao; Mohamed, Maryati; Meleng, Paulus (Zootaxa, 2023)
The genus Utivarachna Kishida, 1940 currently comprises 23 species, with eight described from Borneo. We examined the type materials of the Bornean species, except for U. fukasawana Kishida, 1940, as well as newly collected specimens. As a result, we describe a new species, Utivarachna itiokai sp. nov., which belongs to the dusun-group. We also provide the first description of the female of Utivarachna ichneumon and redescribe the known Utivarachna species of Borneo.